On the local theory of geodesic curves congruence in the Euclidian connections spaces - Bliznikienė, I. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Близникене, К локальной теории конгруэнций геодезических кривых пространства евклидовой связностиI. Bliznikienė, Euklidinio sąryšio erdvės geodezinių kreivių kongruencijos lokalinės teorijos klausimu